Mii maanda ezhi-gkendmaanh : niibing, dgwaagig, bboong, mnookmig dbaadjigaade maanpii mzin'igning - Luby, Brittany (Groundwood Books/House of Anansi Press, 2021)
"In this lyrical story-poem, written in Anishinaabemowin and English, a child and grandmother explore their surroundings, taking pleasure in the familiar sights that each new season brings. We accompany them through warm summer days full of wildflowers, bees and blueberries, then fall, when bears feast before hibernation and forest mushrooms are ripe for harvest. Winter mornings begin in darkness as deer, mice and other animals search for food, while spring brings green shoots poking through melting snow and the chirping of peepers."--